Unsuspected uterine leiomyosarcoma: magnetic resonance imaging findings before and after focused ultrasound surgery. Issue 3 (1st May 2007) - Fukunishi, H.; Funaki, K.; Ikuma, K.; Kaji, Y.; Sugimura, K.; Kitazawa, R.; Kitazawa, S.
Abstract : Uterine leiomyosarcoma, initially diagnosed as leiomyoma on magnetic resonance (MR) images, was disclosed after focused ultrasound surgery (FUS). The tumor did not display high signal intensity on either T1- or T2-weighted images on the patient's first visit. Four months thereafter, T2-weighted images revealed a high signal intensity area within the tumor, while T1-weighted images showed low signal intensity. Six months after FUS, the nonperfused volume calculated on meglumine gadoterate-enhanced T1-weighted images decreased markedly and an intermediate signal intensity in a circular area on T2-weighted images appeared to be atypically increasing in volume. After laparoscopic myomectomy, this tumor was diagnosed as uterine leiomyosarcoma coexistent with leiomyoma. The early stages of uterine leiomyosarcoma are clinically difficult to diagnose; therefore, both careful monitoring during FUS and close follow-up after the procedure are vital.